Innate lymphoid cells drive interleukin-23-dependent innate intestinal pathology. - Buonocore, S; Ahern, P; Uhlig, H; Ivanov, I; Littman, DR; Maloy, K; Powrie, F (2010)
The key role of interleukin (IL)-23 in the pathogenesis of autoimmune and chronic inflammatory disorders is supported by the identification of IL-23 receptor (IL-23R) susceptibility alleles associated with inflammatory bowel disease, psoriasis and ankylosing spondylitis. IL-23-driven inflammation has primarily been linked to the actions of T-helper type 17 (TH17) cells. Somewhat overlooked, IL-23 also has inflammatory effects on innate immune cells and can drive T-cell-independent colitis. However, the downstream cellular and molecular pathways involved in this innate intestinal inflammatory response are poorly characterized. Here we show that bacteria-driven innate colitis is associated with an increased production of IL-17 and interferon-gamma in the colon. Stimulation of colonic leukocytes with IL-23 induced the production of IL-17 and interferon-gamma exclusively by innate lymphoid cells expressing Thy1, stem cell antigen 1 (SCA-1), retinoic-acid-related orphan receptor (ROR)-gammat and IL-23R, and these cells markedly accumulated in the inflamed colon. IL-23-responsive innate intestinal cells are also a feature of T-cell-dependent models of colitis. The transcription factor ROR-gammat, which controls IL-23R expression, has a functional role, because Rag-/-Rorc-/- mice failed to develop innate colitis. Last, depletion of Thy1+ innate lymphoid cells completely abrogated acute and chronic innate colitis. These results identify a previously unrecognized IL-23-responsive innate lymphoid population that mediates intestinal immune pathology and may therefore represent a target in inflammatory bowel disease.